Implementation of Column Formwork Works on the 10th Floor in the Construction of Sky House Alam Sutera Phase 3 Building - Ghani Leo Frando; Mulya, Eka Sasmita (Yayasan Kawanad, 2025)
Formwork is a crucial component in reinforced concrete structural works. This study specifically discusses the application of aluminum formwork for column elements in high-rise buildings. Time inefficiency and quality issues encountered when using wooden or conventional formwork are major problems frequently found on construction sites. This study aims to identify the advantages and disadvantages of using aluminum formwork for columns and to evaluate its impact on construction time and the quality of the resulting product. The research employed a qualitative descriptive approach through direct observation and interviews with workers and project managers at the Sky House Alam Sutera Phase 3 building project. The results show that aluminum formwork can be installed and dismantled faster than wooden formwork, and it produces a smoother and more precise concrete surface. However, aluminum formwork has a higher initial procurement cost. Nevertheless, it is more cost-effective in the long term if properly maintained and reused multiple times. Due to its efficiency, neatness, and durability, aluminum formwork is a suitable choice for high-rise building projects.